1983
DOI: 10.1007/bf01259236
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Prokto-Colektomie mit Ileum-Pouch

Abstract: A metabolic and functional assessment was carried out in 7 patients, who had undergone a restorative proctocolectomy with pelvic ileal pouch (Parks S-Pouch) between 8 and 38 months previously. The average follow-up was 22,5 months. The symptoms which led to the operation were in all patients ulcerative colitis. The mean faecal output per 24 h was 425.7 +/- 104 g, and the mean reservoir volume 233.5 +/- 102.3 ml. Within 24 h the average number of bowel movements has been 4.5 +/- 1.05 (range 3 to 6). One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…29,36 The deprivation of systematic transferrin in these patients corresponded with iron deficiency anemia. 7,36 Other researchers 40,41 have observed normal referenced transferrin values during the same phases.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…29,36 The deprivation of systematic transferrin in these patients corresponded with iron deficiency anemia. 7,36 Other researchers 40,41 have observed normal referenced transferrin values during the same phases.…”
Section: Resultsmentioning
confidence: 87%
“…7 Similar observations were noted by others. 38,40 Nicholls et al . 6 reported that of their 14 RPC-patients, 2 (14.5 percent) cases showed folate concentration below referenced level, but all had normal red cell folate values.…”
Section: Folate Deficiency Anemiamentioning
confidence: 99%